Analisa Digital Forensik Rekaman Video CCTV dengan Menggunakan Metadata dan Hash - Irfansyah Noor Prawiranegara; Gregorius Hendita Artha Kusuma (Ikatan Ahli Informatika Indonesia, 2019)
The development of technology is developing rapidly and has many positive effects and various conveniences. As the development of the digital world today with the sophistication of the device, one example is CCTV (Closed Circuit Television). Its use has been widely applied in Indonesia such as supermarkets, shopping places as well as other public places. CCTV has an important role in the field of security, many of which are used as evidence in the legal field to prove various legal issues, this is where the role of Digital Forensics is needed to support investigations and search for evidence. can be known as genuine or not by using hashing techniques or methods that analyze the arithmetic transformation of a series of characters into their original values.